Household food security and diet quality with chronic energy deficiency among preconception women - Pradita Putri Ramadhani; Fillah Fithra Dieny; Dewi Kurniawati; Hartanti Sandi; Deny Yudi Fitranti; Ayu Rahadiyanti; A. Fahmy Arif Tsani (Jurnal Gizi Indonesia: The Indonesian Journal of Nutrition, 2021)
Background: Chronic energy deficiency (CED) that occurs at risk preconception women during pregnancy increased low birth weight (LBW) in infants. Household food security and diet quality are factors that cause CED. Therefore, this study aims to determine the relationship between household food security and diet quality with CED preconception women.